Copper inducing effect on laccase production of white rot fungi native from Misiones (Argentina) - Fonseca, Maria Isabel; Shimizu, Ernesto; Zapata, Pedro Dario; Villalba, Laura (Enzyme and Microbial Technology)
Fungi may be selected as models for gene expression studies and further adaptation for biotechnological enzyme production. The aim of this work was to evaluate laccase production and to analyze the effect of Cu 2+ on selected fungi natives of Misiones, Ganoderma applanatum (strain F), Peniophora sp. (BAFC 633), Pycnoporus sanguineus (BAFC 2126) and Coriolus versicolor f. antarcticus (BAFC 266).Fungi secretion system of G. applanatum, Peniophora sp., P. sanguineus and C. versicolor f. antarcticus is sensitive to stimulation by copper. Biomass values of G. applanatum, Peniophora sp. and C. versicolor f. antarcticus did not show differences between treatments. P. sanguineus biomass underwent a dramatic growth inhibition with 1mM Cu 2+ and marked delay in growth with 0.5mM Cu 2+. Proteins were increased with copper in Peniophora sp., C. versicolor and G. applanatum. G. applanatum and Peniophora sp. reached the highest enzyme activity at 10th day equivalent to 49.2-fold and 19.7-fold higher than the control samples, respectively. Copper produced an increase of constitutive laccases in all fungi and an additional inducible isoenzyme in Peniophora sp., C. versicolor f. antarcticus and G. applanatum. © 2010 Elsevier Inc. Fil: Fonseca, Maria Isabel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Misiones. Facultad de Ciencias Exactas Químicas y Naturales. Departamento de Bioquímica Clínica. Laboratorio de Biotecnología Molecular; Argentina Fil: Shimizu, Ernesto. Universidad Nacional de Misiones. Facultad de Ciencias Exactas Químicas y Naturales. Departamento de Bioquímica Clínica. Laboratorio de Biotecnología Molecular; Argentina Fil: Zapata, Pedro Dario. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Misiones. Facultad de Ciencias Exactas Químicas y Naturales. Departamento de Bioquímica Clínica. Laboratorio de Biotecnología Molecular; Argentina Fil: Villalba, Laura. Universidad Nacional de Misiones. Facultad de ...